2013
DOI: 10.1117/1.jbo.18.9.096007
|View full text |Cite
|
Sign up to set email alerts
|

Visible spatial frequency domain imaging with a digital light microprojector

Abstract: Abstract. There is a need for cost effective, quantitative tissue spectroscopy and imaging systems in clinical diagnostics and pre-clinical biomedical research. A platform that utilizes a commercially available light-emitting diode (LED) based projector, cameras, and scaled Monte Carlo model for calculating tissue optical properties is presented. These components are put together to perform spatial frequency domain imaging (SFDI), a model-based reflectance technique that measures and maps absorption coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…DOS is a relatively novel imaging modality in the field of breast cancer and is rapidly evolving by increasing spatial resolution and by increasing analytic techniques to provide more accurate assessment of functional parameters (28,29). A recent study by Roblyer and colleagues indicated that DOS as early as the first day after NAC may possibly discriminate nonresponding from responding patients (30).…”
Section: Discussionmentioning
confidence: 99%
“…DOS is a relatively novel imaging modality in the field of breast cancer and is rapidly evolving by increasing spatial resolution and by increasing analytic techniques to provide more accurate assessment of functional parameters (28,29). A recent study by Roblyer and colleagues indicated that DOS as early as the first day after NAC may possibly discriminate nonresponding from responding patients (30).…”
Section: Discussionmentioning
confidence: 99%
“…55,56 In the visible wavelength regime, the thinned skull and underlying cerebral spinal fluid take up a higher partial volume fraction, diluting the perceived scattering from the brain. Differences in thin skull preparation, as well as the effect of saline on the skull, 24 could also account for the variability in μ 0 s measured with visible-SFDI, ameliorating the difference between control and 3xTg-AD brains seen with NIR-SFDI.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline oxy-and deoxyhemoglobin values were calculated from the corrected μ a values using least-squares linear fit of the Beer-Lambert law as before. 24 …”
Section: Correction Factor For Baseline μ Amentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed for generated periodic illumination patterns to be imaged onto the tissue samples. The sinusoidal images were corrected according to the projector response function using a similar method as described by Lin et al 18 A custom program written in Python synchronized image acquisition along with presentation slide rotation by employing Active Python and the Windows COM API (Microsoft Inc.). Each scan produced a data-cube, which comprised a reflectance image for 240 wavelengths between 400 and 900 nm (Fig.…”
Section: Spatial Frequency Domain Imaging Systemmentioning
confidence: 99%